Independent Community Pharmacy Stakeholder-Informed Dispensing Fee Reform: A Cross-Sectional Survey. - Ziyanda Ndlangisa; Vivian Naidoo; Ruwayda Petrus; Sarentha Chetty; Varsha Bangalee (Student's Journal of Health Research Africa, 2026)
Background: The South African four-tier dispensing fee was formally implemented in 2010. The fee structure was determined using a zero-based model and a return-on-investment dispensary cost, with the assumption that a well-run pharmacy dispenses 2300 items per month. The fee structure has significant implications for the viability of independent community pharmacies. Objectives: To quantitatively examine the current dispensing fee structures' influence on service delivery at independent community pharmacies in the KwaZulu-Natal province and to propose independent community pharmacy stakeholder-informed priorities for fee revision. Methods: A descriptive cross-sectional online survey was conducted between 5 December 2025 and 28 February 2026 among pharmacy owners, responsible pharmacists, and pharmacists working at independently owned pharmacies in the KwaZulu-Natal province. Chi-square tests were used to assess associations, and a binary logistic regression was used to identify predictors. All data analysis was done at a level of significance. Results: Male respondents represented 58.2% of the sample, with female respondents representing 41.8%. The majority of the respondents were from peri-urban locations (48.6%). Sixty-one of the 146 respondents (41.8%) reported service changes in response to the fee structure. Pharmacies dispensing less than 2300 items per month were more likely to offer additional services than those dispensing at/above 2300. Years of community pharmacy experience were a significant predictor of service adaptation (AOR 6.13; 95% CI 1.013-1.114, p=0.13). Conclusion: Survey findings suggest the current dispensing fee structure may be context-blind, with respondents dispensing below the 2300 items per month threshold being pushed to adopt innovative strategies to ensure practice viability. Respondents with more years of experience were more likely to provide additional services at their pharmacies. Recommendations: The fee structure needs to incorporate actual pharmacy operational costs and location. Future research should consider adopting qualitative methods to explore viable options to align the dispensing fee structure with actual pharmacy operations.